Financial futures - Fitzgerald, M. Desmond (London : Euromoney Publications, 1983)
This book covers the explosion of futures trading outside its traditional homeland of the United States.
Includes bibliographical references (p. 195-197) and index.
aia 16/05/13
Loan
Keywords: Financial futures; Hedging (Finance); Foreign exchange futures; Speculation; Interest rate futures; Commodity exchanges